Stateczność Niejednorodnej, Grubościennej Rury Poddanej Skończonym Odkształceniom - Regiński, K. (Engineering Transactions, 1973)
On the basis of the kinetic criterion of instability, the equation of equilibrium of a nonhomo-geneous, axially symmetric body has been derived. The problem of determination of the critical strains is then reduced to a linear, self-adjoint boundary value problem which is solved numerically, The conditions of stability loss are analyzed, depending on various geometric and material parameters of the body.